Public communication of the political opposition in Cuba: inquiries for the state of the issue - Celecia, Cosette (2019)
Interest here is to establish a state of the issue on public communication of the political opposition in Cuba, because in the reviews on the subject no studies relating both terms were found. Meanwhile, there are few studies that examine Cuban dissidence in general. To advance in research about how is the configuration of the public thing is set around the political opposition in Cuba, an illegal and criminalized activity, is imposed an analysis that identifies gaps in knowledge production about this subjects and rescue the elements which allow us to think, contextualized and critically, the phenomenon.